Ogniskowa proliferacja nabłonka barwnikowego siatkówki jako czynnik ryzyka rozwoju utajonej neowaskularyzacji naczyniówkowej - Święch-Zubilewicz, Anna; Dolar-Szczasny, Joanna; Żarnowski, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To evaluate the relationship between isolated focal retinal pigment epithelium (RPE) proliferation and development of occult choroidal neovascularisation. Material and methods: The natural clinical course of 43 eyes of 39 patients was analyzed. Patients with RPE proliferation as an isolated manifestation of retinal degeneration were included in this study. The mean age of patients was 75.0 (69-94). The mean observation period was 41.4 months (6-63). Results: In 30 eyes (70%), occult choroidal neovascularisation occurred, in 13 eyes (30%), that complication was not observed. The development of neovascularisation was correlated with the presence of neovascular membrane in the fellow eye. Conclusions: Based on presented data we can estimate that isolated focal proliferation of retinal pigment epithelium is an important risk factor for the development of occult choroidal neovascularisation.